Thick film resistor paste, thick film resistor, and electronic component
The use of a thick film resistance paste with lutetium oxide and controlled glass components addresses surge resistance and TCR issues in miniaturized resistors, enhancing stability and uniformity for electronic components.
Patent Information
- Application Number
- JP2022518159
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2020-05-01
- Filing Date
- 2021-04-30
- Publication Date
- 2025-01-28
- Estimated Expiration
- 2041-04-30
AI Technical Summary
Thick film resistors, particularly those used in miniaturized electronic components, face challenges in achieving high surge resistance due to localized heating and resistance value changes when subjected to surge voltage, and there are limitations in adjusting the resistance temperature coefficient (TCR) and conductor distribution uniformity.
A thick film resistance paste composed of lutetium oxide and lutetium oxide with specific glass components and additives, such as silicon oxide, lead oxide, and boron oxide, is used to form a conductor-containing glass powder with controlled particle sizes and ratios, enhancing surge resistance and TCR adjustment.
The solution provides thick film resistors with improved surge resistance and controlled TCR, ensuring stable resistance values under surge conditions and maintaining uniform conductor distribution, suitable for miniaturized electronic components.
Smart Images

Figure 0007622736000001 
Figure 0007622736000002 
Figure 0007622736000003
Abstract
Description
[Technical field]
[0001] The present invention relates to a thick-film resistor paste, and more specifically, to a thick-film resistor paste that contains glass powder containing ruthenium oxide and lead ruthenate as conductive materials and that can form a thick-film resistor having particularly excellent surge resistance, a thick-film resistor using the thick-film resistor paste, and an electronic component equipped with the thick-film resistor. [Background technology]
[0002] A thick-film resistor paste is generally composed of conductive powder, glass powder, and an organic vehicle for forming them into a paste suitable for printing. This thick-film resistor paste is printed in a desired pattern, and the glass is sintered at a high temperature of usually 800 to 1000°C, and is used as a thick-film resistor that constitutes an electronic component such as a thick-film chip resistor. Ruthenium oxide powder and lead ruthenate powder are widely used as the conductive powder, since the resistance value can be changed gradually by adjusting the mixing ratio with the glass powder.
[0003] For example, Patent Document 1 discloses a resistor obtained by adding a vehicle using ethyl cellulose as a binder and toluene and alcohol as a solvent to a mixture using mullite as inorganic particles, lead borosilicate glass as glass particles, and ruthenium dioxide as conductive particles. Anti-pe The technology for forming thick film resistors using a paste is described.
[0004] Patent Document 2 describes a resistor obtained by adding a vehicle using ethyl cellulose as a binder and terpineol and butyl carbitol acetate as a solvent to a mixture using zircon as inorganic particles, borosilicate lead glass as glass particles, and ruthenium dioxide as conductive particles. Anti-pe The technology for a thick-film resistor formed using the resistive paste is also described.
[0005] In recent years, electronic components such as thick-film chip resistors have become smaller, and thick-film resistors are required to have improved electrical properties. In particular, thick-film resistors with excellent voltage resistance, such as surge resistance, are required. When a momentary high voltage (surge voltage) is applied to a thick-film resistor, it usually shows a negative resistance change, but it is desirable for this resistance change to be small. Such a negative resistance change is thought to be the effect of heat generation when voltage is applied. In conventional thick-film resistor pastes, glass powders are bonded together during sintering, but the softening of the glass powder is limited to the surface layer. Therefore, in the thick-film resistor after sintering the thick-film resistor paste, a dielectric layer equivalent to the glass particle diameter exists. The conductive powder is distributed around this dielectric layer, giving the thick-film resistor conductivity. It is thought that when a surge voltage is applied to such a structure, a current flows through the conductive part, the surrounding area is locally heated, and a resistance change occurs.
[0006] One method for improving the surge resistance of thick-film resistors is to increase the amount of lead ruthenate contained in the thick-film resistor paste. By increasing the amount of lead ruthenate contained in the thick-film resistor paste, a thick conductive path and a strong conductive part are formed in the thick-film resistor after sintering the thick-film resistor paste, which is thought to suppress heat generation when a surge voltage is applied and mitigate the effect of changes in resistance value. However, increasing the amount of lead ruthenate increases the temperature coefficient of resistance (TCR). TCR indicates the rate of change in resistance per unit temperature, and is one of the important characteristics of thick-film resistors. If the TCR increases by increasing the amount of lead ruthenate, even if the change in resistance due to heat generation when a surge voltage is applied is suppressed, the resistance of the conductive part itself will change. For this reason, when increasing the amount of lead ruthenate, it is necessary to bring the TCR closer to 0. This TCR can be adjusted by adding an additive, mainly made of a metal oxide, to the thick-film resistor, and examples of the metal oxide include manganese oxide, niobium oxide, and titanium oxide. However, there is a limit to the degree to which the additive can be adjusted, and therefore there is also a limit to the amount of lead ruthenate that can be increased.
[0007] Another method for improving the surge resistance of thick-film resistors is to make the distribution of conductors in the resistor more uniform. If the distribution of conductors is made uniform, current will flow uniformly through the resistor when a surge voltage is applied, and the effect of localized heat generation can be mitigated. [Prior art documents] [Patent documents]
[0008] [Patent Document 1] Japanese Patent Application Publication No. 4-320003 [Patent Document 2] Japanese Patent Application Publication No. 6-163202 Summary of the Invention [Problem to be solved by the invention]
[0009] However, in recent years, thick-film resistors for electronic components have become increasingly smaller, and therefore higher surge resistance is required. An object of the present invention is to provide a thick-film resistor paste for resistors having a smaller rate of resistance change and excellent surge resistance for electronic components that are becoming increasingly smaller, a thick-film resistor using the thick-film resistor paste, and an electronic component equipped with the thick-film resistor. [Means for solving the problem]
[0010] As a result of various studies, the inventors of the present invention discovered that a thick-film resistor formed from a thick-film resistor paste using a conductive glass made of ruthenium oxide and lead ruthenate having a specific composition has better surge resistance than conventional resistors, leading to the development of the present invention.
[0011] That is, the thick-film resistor paste according to the present invention contains a glass powder containing a conductive material consisting of ruthenium oxide and lead ruthenate, and an organic vehicle, and the conductive material-containing glass powder is Ruthenium oxide: 0.4% by mass or more and 2.7% by mass or less; lead ruthenate: 9.6% by mass or more and 67.3% by mass or less The glass composition contains silicon oxide relative to 100% by mass of the glass component. 33% or more by mass and 60% or less by mass of silicon oxide, 30% or more by mass and 90% or less by mass of lead oxide, and 5% or more by mass and 50% or less by mass of boron oxide, and the total content of silicon oxide, lead oxide, and boron oxide is 50% or more by mass relative to 100% by mass of the glass component.
[0012] In the thick-film resistor paste of the present invention, the conductive material-containing glass powder preferably has an average particle size of 5 μm or less.
[0013] A thick film resistor according to the present invention is characterized in that it is made of a sintered body of any one of the thick film resistor pastes according to the present invention.
[0014] Moreover, an electronic component according to the present invention is characterized by comprising the above-mentioned thick-film resistor according to the present invention. Effect of the Invention
[0015] According to the present invention, it is possible to provide a thick-film resistor paste having better surge resistance than conventional thick-film resistors, a thick-film resistor using the thick-film resistor paste, and an electronic component including the thick-film resistor. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0016] Hereinafter, an embodiment of the present invention will be described, however, the present invention is not limited to the following embodiment, and various modifications and substitutions can be made to the following embodiment within the scope of the present invention. The thick-film resistor paste of this embodiment contains glass powder containing conductive materials made of ruthenium oxide and lead ruthenate, and an organic vehicle. Each component will be described in detail below.
[0017] (Conductive material) The conductive material in the thick-film resistor paste of the present invention is a mixed conductive material consisting of ruthenium oxide and lead ruthenate. A typical thick-film resistor paste has a structure containing a conductive material and glass in powder form, but the thick-film resistor paste of the present invention does not use a single conductive material, but contains a conductive-material-containing glass powder obtained by crushing a conductive-material-containing glass produced using a mixed conductive material powder consisting of conductive ruthenium oxide powder and lead ruthenate powder as part of the raw material. The particle size of lead ruthenate used to form the conductive glass powder is not particularly limited, but it is preferable that the specific surface area is less than 5 m 2 It is desirable to have a particle size of 5 m / g or more. 2 If the particle size is less than 1.0 μm / g, the particle size of lead ruthenate is too large, which may reduce the uniformity of the conductive area in the thick-film resistor and deteriorate the surge resistance. The particle size of the ruthenium oxide used to form the conductive glass powder is not particularly limited, but it is preferable that the specific surface area is 20 m 2 It is desirable to have a particle size of 20 m 2 If it is less than 1.0 μm / g, the particle size of the ruthenium oxide will be too large, which may reduce the uniformity within the thick-film resistor and deteriorate the surge resistance.
[0018] (Glass component) The glass component used in the conductive material-containing glass in the thick-film resistor paste of the present invention contains silicon oxide (SiO2), lead oxide (PbO) and boron oxide (B2O3). In addition, magnesium oxide (MgO), calcium oxide (CaO), barium oxide (BaO), strontium oxide (SrO), cadmium oxide (CdO), tin oxide (SnO), zinc oxide (ZnO), bismuth oxide (Bi2O3), etc. may be contained. Aluminum oxide (Al2O3) may also be contained.
[0019] (Silicon oxide: SiO2) SiO2 is a component that forms the framework of the glass component of the present invention, and the blending amount is 3% by mass or more and 60% by mass or less with respect to 100% by mass of the glass component contained in the conductive material-containing glass. If it is more than 60% by mass, the softening point of the glass formed will be too high. Also, if it is less than 3% by mass, a chemically stable glass cannot be obtained.
[0020] (Lead oxide: PbO) PbO lowers the softening point, promotes wetting with ruthenium oxide, and increases dispersibility, and also chemically stabilizes lead ruthenate and inhibits its decomposition. The blending amount is 30% to 90% by mass relative to 100% by mass of the glass components contained in the conductive glass. If it is less than 30% by mass, the softening point of the glass formed will be too high. If it is more than 90% by mass, it will be difficult to obtain a chemically stable glass state.
[0021] (Boron oxide: B2O3) B2O3, together with SiO2, is a component that forms the framework of the glass component of the present invention, and has the effect of lowering the softening point of the glass formed. The blending amount is 5% by mass or more and 50% by mass or less with respect to 100% by mass of the glass component contained in the conductive material-containing glass. If it is less than 5% by mass, the toughness of the glass formed decreases, cracks are easily generated, and the laser trimming properties deteriorate. If it is more than 50% by mass, phase separation of the glass component is easily caused, and water resistance also decreases.
[0022] (Total content of essential glass components) The total content of SiO2, PbO, and B2O3 is 50% by mass or more relative to 100% by mass of the glass component contained in the conductive glass. If the total content is less than 50% by mass, it is difficult to stably form the glass, and it is difficult to satisfy the surge resistance in the electrical properties of the thick-film resistor of the present invention.
[0023] (Other glass components) In addition to the above essential glass components, oxides may be further contained as glass components to improve various properties, within the range that does not deteriorate the properties of the conductive glass. Specifically, Al2O3, MgO, CaO, BaO, SrO, CdO, SnO, ZnO, Bi2O3, etc. may be contained. The blending amount of these glass components is 20 mass% or less for each of 100 mass% of the glass components contained in the conductive glass.
[0024] (Conductive glass) In the conductive glass used in the thick-film resistor paste of the present invention, the blending ratio of the conductive material and the glass component is 10% by mass to 70% by mass, and 30% by mass to 90% by mass of the glass component, relative to 100% by mass of the conductive glass composition. If the conductive material is less than 10% by mass, the resistance value of the conductive glass powder produced is too high and it shows almost no conductivity. If the conductive material is more than 70% by mass, the glass component cannot cover the conductive powder, and the conductive glass becomes brittle. By adjusting the blending ratio of the conductive material and the glass component, it is possible to adjust the resistance value of the thick-film resistor to the vicinity of the target resistance value. By changing the blending ratio of ruthenium oxide and lead ruthenate, the resistance value and TCR can be adjusted in more detail. Since the TCR has a limited range of adjustment, it is necessary to adjust the blending ratio of ruthenium oxide and lead ruthenate to obtain the desired TCR. The conductive glass is pulverized to an average particle size of 5 μm or less. If the average particle size is larger than 5 μm, the uniformity of the thick film resistor decreases, and there is a risk that the improvement effect of the surge resistance cannot be obtained, which is not preferable. The pulverization method can be a ball mill, a planetary mill, a bead mill, etc. In the present invention, the average particle size means the median diameter, and is a value measured by ultrasonically dispersing the powder to be measured in a 2 g / L aqueous solution of sodium hexametaphosphate and using a particle size distribution meter (HPA9320-100X, manufactured by Microtrackbell) using pure water as a solvent.
[0025] (Other additives) The thick-film resistor paste of the present invention may further contain borosilicate glass that does not contain conductive materials and commonly used additives for the purpose of adjusting and improving the resistance value, TCR, and other characteristics of the thick-film resistor. In addition, a dispersant may be contained as an additive to improve dispersibility. Main additives include niobium oxide (Nb2O5), tantalum oxide (Ta2O5), titanium oxide (TiO2), copper oxide (CuO), manganese oxide (MnO2), zirconium oxide (ZrO2), aluminum oxide (Al2O3), etc. The content of the additives can be adjusted according to the desired improved characteristics, but it is preferably 10 mass% or less in the total amount of inorganic substances of 100 mass%.
[0026] (Organic Vehicle) The organic vehicle used in the thick-film resistor paste of the present invention is not particularly limited, and may be one in which a resin such as ethyl cellulose or rosin is dissolved in a solvent such as terpineol, which is used in general resistor pastes. The amount of the organic vehicle may be appropriately adjusted depending on the printing method, etc., but is generally 20% by mass or more and 50% by mass or less with respect to the total amount of the resistor paste, 100% by mass.
[0027] (Method of manufacturing thick film resistor paste) The method for producing a thick-film resistor paste by mixing the conductive material-containing glass and the organic vehicle, and optionally adding lead borosilicate glass powder and additives, is not particularly limited, and a general three-roll mill, a bead mill, or the like can be used.
[0028] (Manufacturing method of thick film resistors) The obtained thick-film resistor paste is printed on a ceramic substrate, the organic solvent is removed by drying treatment, and then the substrate is fired at a temperature of, for example, 800° C. to 900° C. to obtain a thick-film resistor. EXAMPLES
[0029] The present invention will be described below in more detail with reference to examples, but the present invention is not limited to these examples.
[0030] (Example 1: Evaluation of a resistor with a sheet resistance of 1 kΩ) The glass material was mixed in a ratio of 48 mass%, 2 mass% ruthenium oxide, and 50 mass% lead ruthenate, melted, and then cooled to produce conductive glass. The glass composition of the conductive glass produced was 33 mass% SiO2, 46 mass% PbO, 5 mass% Al2O3, 7 mass% B2O3, 3 mass% ZnO, and 6 mass% CaO relative to 100 mass% of the glass components. The obtained conductive material-containing glass was pulverized in a ball mill to an average particle size of about 1 μm. A thick-film resistor composition containing 59% by mass of conductive material-containing glass powder, 1% by mass of Nb2O5 as an additive, and the remainder being an organic vehicle was kneaded in a three-roll mill so that various inorganic materials were dispersed in the organic vehicle, to prepare the thick-film resistor paste of Example 1. The organic vehicle used was a solution of 20 parts by mass of ethyl cellulose dissolved in 100 parts by mass of terpineol. The composition of the thick-film resistor paste of Example 1 and the composition of the conductive material-containing glass used to manufacture the thick-film resistor paste are shown in Table 1.
[0031] <Evaluation test> (Preparation of evaluation samples) The thick-film resistor paste thus prepared was printed with a width of 1.0 mm between five pairs of electrodes spaced 1.0 mm apart on an alumina substrate in advance, and then dried in a belt furnace at a peak temperature of 150°C for 5 minutes. It was then fired in a belt furnace at a peak temperature of 850°C for 9 minutes. Five samples were prepared in the same manner, each for an alumina substrate, to obtain thick-film resistors (total of 25 pieces) for evaluation.
[0032] (film thickness measurement) The film thickness was measured by using a stylus-type surface roughness tester to randomly select one alumina substrate from the evaluation samples, measure the film thickness of each of the five thick-film resistors, and record the average value of the five points as the actual measured film thickness.
[0033] (Converted area resistance value) The resistance values at 25°C of five evaluation samples (total of 25 samples) formed on five alumina substrates were measured using a circuit meter (2001 MULTIMETER, manufactured by KEITHLEY), and the average value was taken as the actual measured resistance value. The converted sheet resistance value when the film thickness was set to 7 μm was calculated using the following formula (1). The calculated converted sheet resistance values are shown in Table 1. 3 As shown in. Converted sheet resistance (kΩ) = measured resistance (kΩ) × (measured film thickness (μm) / 7 (μm)) (1)
[0034] (High temperature coefficient of resistance: High temperature TCR) The resistance values of five thick-film resistors formed on an alumina substrate as evaluation samples were measured after being held in a thermostatic chamber at 25°C and 125°C for 30 minutes. The measured resistance values were designated as R 25 , R 125 The high-temperature TCR was calculated using the following formula (2). The average value of the calculated high-temperature TCR at five points is shown in Table 3. High temperature TCR (ppm / ℃)=[(R 125 -R 25 ) / R 25 ] / (100)×10 6 (2)
[0035] (Evaluation of trimming ability) A glass material containing 30% by mass of SiO2, 55% by mass of PbO, 5% by mass of Al2O3, and 10% by mass of B2O3 was kneaded by a three-roll mill so as to be dispersed in an organic vehicle of the same composition as that used in Example 1, to prepare a glass paste. The glass paste was applied so as to cover the thick-film resistor of the evaluation sample, and dried in a belt furnace at a peak temperature of 150°C for 5 minutes. Then, the resistor was fired in a belt furnace at a peak temperature of 600°C for 5 minutes. The resistance value of the thick-film resistor covered with the glass paste was set to the initial resistance value Rs(t), and laser trimming was performed using a laser trimming device (SL432R, manufactured by Omron Laserfront Co., Ltd.) so as to obtain a resistance value 1.5 times that of Rs(t). The laser trimming conditions were straight cut, cut speed 100 mm / sec, laser intensity 2 W, and Q rate 6 kHz. The resistance value after trimming was designated as Re(t), and the percentage of the resistance value deviation before and after trimming was calculated using the following equation (3). Resistance deviation (%) = (Re(t) - 1.5 × Rs(t)) / Rs(t) × 100 (3) If even one of the five thick film resistors had a resistance value deviation of 1% or more, the trimming ability was rated as "X", and if all resistance value deviations were less than 1%, the ability was rated as "O". The evaluation results are shown in Table 3.
[0036] (Surge resistance evaluation: resistance change rate) When the trimming property was evaluated as "good", an electrostatic discharge test was performed on the thick-film resistor of the evaluation sample using a semiconductor device electrostatic tester (ESS-6008, manufactured by Noise Laboratory) to apply a voltage under the conditions of a capacitance of 200 pF and an internal resistance of 0 Ω. A voltage of 5 kV was applied to the thick-film resistor of the evaluation sample five times at one-second intervals, and the resistance value Rs before and the resistance value Re after the voltage application were measured, and the resistance change rate was calculated using the following formula (4). The average resistance change rate calculated at five points is shown in Table 3. Resistance change rate (%) = (Re-Rs) / Rs × 100 (4)
[0037] (Examples 2 to 12) The glass material, ruthenium oxide, and lead ruthenate were mixed in the ratios shown in Table 1, melted, and then cooled to prepare conductive glass. The glass composition of each conductive glass prepared was as follows: SiO 2 , PbO, Al 2 O 3 、B 2 O 3 The contents of ZnO and CaO are as shown in Table 1. Each of the obtained conductive material-containing glasses was pulverized in a ball mill to have an average particle size shown in Table 1. A thick-film resistor composition containing a conductive material-containing glass powder, an additive, and an organic vehicle in the ratio shown in Table 1 was kneaded in a three-roll mill so that various inorganic materials were dispersed in the organic vehicle, to prepare thick-film resistor pastes of Examples 2 to 12. The organic vehicle had the same composition as that used in Example 1. Further, thick-film resistors as evaluation samples were prepared in the same manner as in Example 1, and evaluations were carried out in the same manner as in Example 1. The evaluation results are shown in Table 3. It should be noted that Examples 4, 7, 9, and 10 are reference examples.
[0038] Comparative Example 1 A thick-film resistor paste was prepared by a conventional manufacturing method in which conductive material-containing glass was not used, and conductive material and glass were added in powder form. However, when ruthenium oxide powder, lead ruthenate powder, and glass powder were added without using conductive material-containing glass powder obtained by crushing conductive material-containing glass, differences in electrical characteristics (TCR) and the like would occur when adjusting the resistance value to a suitable value for the thick-film resistor paste. Therefore, in Comparative Example 1 prepared by a conventional manufacturing method, the blending amounts of ruthenium oxide powder, lead ruthenate powder, and glass composition, which are added as conductive materials, were changed in order to adjust TCR and the like. That is, a thick-film resistor composition containing 6 mass% ruthenium oxide powder, 17 mass% lead ruthenate powder, 36% glass powder, 1 mass% Nb2O5 as an additive, and the remainder was an organic vehicle was prepared, and the mixture was kneaded by a three-roll mill so that various inorganic materials were dispersed in the organic vehicle, to prepare a thick-film resistor paste of Comparative Example 1. The glass composition in the prepared thick-film resistor paste was 100% by mass of the glass component, with 33% by mass of SiO2, 47% by mass of PbO, 5% by mass of Al2O3, 7% by mass of B2O3, 3% by mass of ZnO, and 5% by mass of CaO. The organic vehicle had the same composition as that used in Example 1. The composition of the thick-film resistor paste in Comparative Example 1 and the composition of the glass used in the manufacture of the thick-film resistor paste are shown in Table 2. Further, thick-film resistors as evaluation samples were prepared in the same manner as in Example 1, and evaluations were carried out in the same manner as in Example 1. The evaluation results are shown in Table 3.
[0039] Comparative Example 2 70% by mass of glass, 5% by mass of ruthenium oxide, and 25% by mass of lead ruthenate were mixed and melted, and then cooled to prepare a conductive glass. The glass composition of the conductive glass thus prepared was 30% by mass of SiO2, 65% by mass of PbO, 2% by mass of Al2O3, and 3% by mass of B2O3, based on 100% by mass of the glass component. The obtained conductive material-containing glass was pulverized in a ball mill to an average particle size of about 1 μm. A thick-film resistor composition containing 69 mass% conductive material-containing glass powder, 2 mass% Mn2O3 as an additive, and the remainder being an organic vehicle was kneaded in a three-roll mill so that various inorganic materials were dispersed in the organic vehicle, to prepare a thick-film resistor paste of Comparative Example 2. The organic vehicle had the same composition as that used in Example 1. Further, thick-film resistors as evaluation samples were prepared in the same manner as in Example 1, and evaluations were carried out in the same manner as in Example 1. The evaluation results are shown in Table 3.
[0040] (Comparative Examples 3 to 10) Conductive glass was prepared by mixing and melting glass material, ruthenium oxide, and lead ruthenate in the proportions shown in Table 1, and then cooling. The glass composition of each conductive glass prepared has the content of SiO2, PbO, Al2O3, B2O3, ZnO, and CaO in the proportions shown in Table 1 relative to 100 mass% of the glass component. Each of the obtained conductive-material-containing glasses was pulverized in a ball mill to have an average particle size shown in Table 1. A thick-film resistor composition containing a conductive-material-containing glass powder, an additive, and an organic vehicle in the ratio shown in Table 1 was kneaded in a three-roll mill so that the various inorganic materials were dispersed in the organic vehicle, to prepare thick-film resistor pastes of Comparative Examples 3 to 10. The organic vehicle had the same composition as that used in Example 1. Further, thick-film resistors as evaluation samples were prepared in the same manner as in Example 1, and evaluations were carried out in the same manner as in Example 1. The evaluation results are shown in Table 3.
[0041] [Table 1]
[0042] [Table 2]
[0043] [Table 3]
[0044] As shown in Table 3, the thick-film resistors of Examples 1 to 12 formed using the thick-film resistor paste prepared using the conductive glass powder of the present invention had a very low rate of change in resistance value before and after the electrostatic discharge test and were found to have excellent surge resistance, compared to the thick-film resistor of Comparative Example 1 formed using the conventional thick-film resistor paste prepared without using the conductive glass powder. In addition, the thick-film resistors of Comparative Examples 2, 6, 8, and 10, which were formed using thick-film resistor pastes obtained using conductive glass made using glass components with a boron oxide content lower than the range claimed in the present invention, were found to have insufficient trimming properties and were not suitable for commercialization. In addition, it was found that the thick-film resistor of Comparative Example 3, which was formed using a thick-film resistor paste obtained using a conductive-material-containing glass having a conductive material content lower than the range claimed in the present invention, had an excessively high resistance value of the conductive-material-containing glass powder and exhibited almost no conductivity. In addition, the thick-film resistor of Comparative Example 4, which was formed using a thick-film resistor paste obtained using a conductive glass having a conductive material content greater than the range of the present invention, was found to have a very high rate of change in resistance value before and after the electrostatic discharge test and to have poor surge resistance. Furthermore, the thick-film resistors of Comparative Examples 5 and 7, which were formed from thick-film resistor pastes obtained using glass components whose silicon oxide or lead oxide contents, or whose total contents of these essential glass components were outside the ranges of the present invention, and the thick-film resistor of Comparative Example 9, which was formed from a thick-film resistor paste obtained using a glass component whose boron oxide content was higher than the range of the present invention, were found to have a higher rate of change in resistance value before and after the electrostatic discharge test and to be inferior in surge resistance compared to the thick-film resistors of Examples 1 to 12.
[0045] From the above test results, it is recognized that the thick film resistor formed using the thick film resistor paste of the present invention has excellent trimming properties and surge resistance, and can be suitably used for electronic components, which have become increasingly miniaturized in recent years.
Claims
1. The glass powder contains a conductive material such as ruthenium oxide and lead ruthenate, and an organic vehicle. The conductive glass powder contains 0.4% by mass or more and 2.7% by mass or less of ruthenium oxide and 9.6% by mass or more and 67.3% by mass or less of lead ruthenate, The glass composition contains 33% by mass or more and 60% by mass or less of silicon oxide, 30% by mass or more and 90% by mass or less of lead oxide, and 5% by mass or more and 50% by mass or less of boron oxide, relative to 100% by mass of the glass component; The total content of silicon oxide, lead oxide, and boron oxide is 50% by mass or more based on 100% by mass of the glass component. A thick film resistor paste comprising:
2. 2. The thick-film resistor paste according to claim 1, wherein the conductive glass powder has an average particle size of 5 [mu]m or less.
3. A thick film resistor comprising a sintered product of the thick film resistor paste according to claim 1 or 2.
4. An electronic component comprising the thick film resistor according to claim 3.
Citation Information
Patent Citations
Resistor
JP1977054195A
Method of manufacturing paste for resistance body
JP1978100496A
Thick film resistor
JP1992320003A
Thick film resistor paste and thick film resistor and manufacturing method thereof
JP1994163202A